2019
DOI: 10.1016/j.epsl.2018.10.016
|View full text |Cite
|
Sign up to set email alerts
|

The roles of climate and human land-use in the late Holocene rainforest crisis of Central Africa

Abstract: There is increasing evidence that abrupt vegetation shifts and large-scale erosive phases occurred in Central Africa during the third millennium before present. Debate exists as to whether these events were caused by climate change and/or intensifying human activities related to the Bantu expansion. In this study, we report on a multi-proxy investigation of a sediment core (KZR-23) recovered from the Congo submarine canyon. Our aim was to reconstruct climate, erosion and vegetation patterns in the Congo Basin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 60 publications
3
21
0
Order By: Relevance
“…This range of εNd values is most characteristic of Precambrian terrains from the Oubanguides flanking the northern Congo Basin, and which is coherent with the dated detrital zircons that shows predominant 1100‐ to 500‐Ma source regions for the sediments (Figures b and c; De Wit & Linol, ; Thiéblemont et al, ). Our results are also in good agreement with those from suspended sediments in the modern river systems (−22.7 < εNd < −9.8), and Holocene deposits in the Congo submarine canyon (−15.6 in average; Bayon et al, ).…”
Section: Resultssupporting
confidence: 87%
“…This range of εNd values is most characteristic of Precambrian terrains from the Oubanguides flanking the northern Congo Basin, and which is coherent with the dated detrital zircons that shows predominant 1100‐ to 500‐Ma source regions for the sediments (Figures b and c; De Wit & Linol, ; Thiéblemont et al, ). Our results are also in good agreement with those from suspended sediments in the modern river systems (−22.7 < εNd < −9.8), and Holocene deposits in the Congo submarine canyon (−15.6 in average; Bayon et al, ).…”
Section: Resultssupporting
confidence: 87%
“…This conclusion is supported by two arguments: (1) We expect a different climatic forcing mechanism than during the AHP, where a precession minimum caused enhanced humidity and the shift of rain belts over the study region (e.g., Costa et al, 2014;Junginger et al, 2014;Bloszies et al, 2015;Beck et al, 2019). For the past ∼5 ka, for example, short-term changes in sea surface temperatures and associated circulation systems could account for these short-term increases in precipitation (e.g., Nicholson, 2017;Bayon et al, 2019). (2) The second argument against maximum water levels in Chew Bahir is that K concentrations do not reach AHP minima.…”
Section: Pace and Magnitude Of Lake Level Changesmentioning
confidence: 72%
“…The studied samples, independently of grain size, display a negative Ce anomaly (Ce/Ce* 0.98, 0.78 for 5863) and notably lower Ce/La ratios ( 1.95, 1.53 for 5863) than observed in any component of the geochemical flux in the Congo basin (Gaillardet et al 1995;Dupré et al 1996). Bayon et al (2019) reported negative Ce anomalies from suspended load in several Congo tributaries and Ce/Ce* values as low as 0.73-0.74 in the Ubangui and Kasai rivers. In Congo sediments, Ce depletion can be ascribed to REE remobilization in soils followed by preferential incorporation of Ce into Fe-oxides, as suggested by the marked positive Ce anomalies shown by river-borne oxyhydroxides (Bayon et al 2004).…”
Section: Intersample Geochemical Variabilitymentioning
confidence: 86%
“…In Congo Fan sand, the strong grain-size control on e Nd values is ascribed to mixing of monazite and other Nd carriers mainly derived from Proterozoic orogenic belts with quartz grains carrying a more negative signature because more durable and thus ultimately derived in larger proportions from Archean cratons. respectively) has not drastically changed throughout the Holocene (Bayon et al 2019).…”
Section: Controls On the Variability Of E Nd Valuesmentioning
confidence: 93%